Activity, Ranging, and Habitat Use Patterns of Two Groups of Boutourline’s Blue Monkeys (Cercopithecus mitis boutourlinii) in Habitats with Different Levels of Anthropogenic Modification in Hamuma Coffee Forest, Ethiopia - Meseret Chane; Afework Bekele; Peter J. Fashing; Colin A. Chapman; Dereje Yazezew; Hussein Ibrahim; Amera Moges; Nga Nguyen; Timothy M. Eppley; Vivek V. Venkataraman; Addisu Mekonnen (International Journal of Primatology, 2026)

Dietary Flexibility of Arsi geladas (Theropithecus gelada arsi) in a Dry, Low-elevation, Human-dominated Landscape at Goro-Jena, Southeast Ethiopia - Amera Moges; Afework Bekele; Peter J. Fashing; Dereje Yazezew; Hussein Ibrahim; Meseret Chane; Nga Nguyen; Vivek V. Venkataraman; Timothy M. Eppley; Addisu Mekonnen (International Journal of Primatology, 2026)

Assessment of predation effects of the wild carnivore towards the livestock in and around Gibe Sheleko National Park, Central Ethiopia - Seyoum Kiros; Afework Bekele (European Journal of Wildlife Research, 2025)
Human-carnivore conflict is a widespread issue, particularly around protected areas such as national parks. This study aimed to evaluate human-carnivore conflict in and around Gibe Sheleko National Park using semi-structured questionnaires. The survey was conducted between December 2018 and August 2020, involving interviews with 281 randomly selected household heads from eight Kebeles and 15 Park management staff. A total of 965 livestock losses were documented over three years, around two animals lost per household per year, with goats being the most affected (48.08%), followed by chickens (33.98%) and cows (13.37%), and sheep were the least affected (1.14%). Of the total livestock losses, the majority (27.15%) were attributed to spotted hyenas (Crocuta crocuta) , followed by serval cats ( Leptailurus serval) (23.21%), and olive baboons ( Papio anubis ) (21.66%). Spotted hyenas (wet: 57.25%, dry: 42.75%), leopards ( Panthera pardus ) (wet: 65.47%, dry: 34.53%), and African wolves ( Canis lupaster ) (wet: 62.24%, dry: 37.76) caused more losses during the wet season. However, the olive baboon (wet: 38.28, dry: 61.72%) and the serval cat (wet: 45.09, dry: 54.91%) caused more losses during the dry season. From the total, about 951 livestock losses (excluding dogs) were reported, resulting in an estimated economic loss of $69,273.65. Goats contributed the largest share ($33,537.92), followed by cattle ($32,634.42) and chickens ($1,423.52). Approximately 62% of respondents reported an increasing trend in livestock predation, particularly by spotted hyenas, olive baboons, and serval cats. Guarding was used by most farmers (80.2%) as a preventative measure against livestock predation; however, it did not work. In the study area, few respondents also applied trapping as a retaliatory killing strategy, which may have a significant impact on existing carnivores. Therefore, collaboration between stakeholders is essential to develop effective mitigation strategies for the ongoing livestock predation by wild carnivores in the area.

Abundance, breeding records, and nest site characteristics of the critically endangered Hooded Vulture (Necrosyrtes monachus) in and around Chelekleka wetland, Ethiopia - Mebrat Teklemariam Gebrekidan; Afework Bekele; Bezawork Afework Bogale (Journal of Ornithology, 2025)

Feeding Ecology of Omo River Guerezas (Colobus guereza guereza) in Natural Versus Plantation Forests in the Central Highlands of Ethiopia - Dereje Yazezew; Afework Bekele; Peter J. Fashing; Nga Nguyen; Hussein Ibrahim; Amera Moges; Timothy M. Eppley; Addisu Mekonnen (International Journal of Primatology, 2024)

Relative abundance and distribution of black-and-white colobus monkey (Colobus guereza guereza) in northwestern Ethiopia - Zewdu Kifle; Afework Bekele (European Journal of Wildlife Research, 2023)

Diet composition of Salt’s dik-dik (Madoqua saltiana Blainville, 1816) in Awash National Park, Ethiopia - Selamawit Geta; Afework Bekele (European Journal of Wildlife Research, 2023)

Feeding ecology of a highland population of hamadryas baboons (Papio hamadryas) at Borena-Sayint National Park, northern Ethiopia - Hussein Ibrahim; Afework Bekele; Peter J. Fashing; Nga Nguyen; Dereje Yazezew; Amera Moges; Vivek V. Venkataraman; Addisu Mekonnen (Primates, 2023)

Publisher Correction: Breeding biology of the helmeted guineafowl (Numida meleagris meleagris, Linnaeus 1758) in Western Ethiopia - Yihenew Aynalem; Afework Bekele; Bezawork Afework Bogale (Ornithology Research, 2023)

Breeding biology of the helmeted guineafowl (Numida meleagris meleagris, Linnaeus 1758) in Western Ethiopia - Yihenew Aynalem; Afework Bekele; Bezawork Afework Bogale (Ornithology Research, 2023)

Population size and habitat preference of the Omo River guereza (Colobus guereza guereza) in a multi-habitat matrix in the central highlands of Ethiopia - Dereje Yazezew; Afework Bekele; Peter J. Fashing; Nga Nguyen; Amera Moges; Hussein Ibrahim; Ryan J. Burke; Timothy M. Eppley; Addisu Mekonnen (Primates, 2022)

Feeding Ecology of the Omo River Guereza (Colobus guereza guereza) in Habitats with Varying Levels of Fragmentation and Disturbance in the Southern Ethiopian Highlands - Dereje Tesfaye; Peter J. Fashing; Anagaw Atickem Meshesha; Afework Bekele; Nils Chr. Stenseth (International Journal of Primatology, 2021)

Distribution and conservation status of Boutourlini’s blue monkey (Cercopithecus mitis boutourlinii), a Vulnerable subspecies endemic to western Ethiopia - Addisu Mekonnen; Peter J. Fashing; Afework Bekele; Nils Chr. Stenseth (Primates, 2020)

Human–Gelada Conflict and Attitude of the Local Community toward the Conservation of the Southern Gelada (Theropithecus gelada obscurus) around Borena Saynit National Park, Ethiopia - Zewdu Kifle; Afework Bekele (Environmental Management, 2020)

Diet and activity patterns of Arsi geladas in low-elevation disturbed habitat south of the Rift Valley at Indetu, Ethiopia - Kelil Abu; Addisu Mekonnen; Afework Bekele; Peter J. Fashing (Primates, 2018)

Ecological Flexibility in Boutourlini’s Blue Monkeys (Cercopithecus mitis boutourlinii) in Jibat Forest, Ethiopia: A Comparison of Habitat Use, Ranging Behavior, and Diet in Intact and Fragmented Forest - Dereje Tesfaye; Peter J. Fashing; Afework Bekele; Addisu Mekonnen; Anagaw Atickem (International Journal of Primatology, 2013)

Population genetic structure and connectivity in the endangered Ethiopian mountain Nyala (Tragelaphus buxtoni): recommending dispersal corridors for future conservation - Anagaw Atickem; Eli K. Rueness; Leif E. Loe; Dimitar Serbezov; Afework Bekele; Nils Chr Stenseth (Conservation Genetics, 2013)

Diet, Activity Patterns, and Ranging Ecology of the Bale Monkey (Chlorocebus djamdjamensis) in Odobullu Forest, Ethiopia - Addisu Mekonnen; Afework Bekele; Peter J. Fashing; Graham Hemson; Anagaw Atickem (International Journal of Primatology, 2010)

Sociological and demographic characteristics of a recently found arsi gelada population in ethiopia - Akio Mori; Toshitaka Iwamoto; Umeyo Mori; Afework Bekele (Primates, 1999)

A case of infanticide in a recently found gelada population in Arsi, Ethiopia - Akio Mori; Toshitaka Iwamoto; Afework Bekele (Primates, 1997)